The Paradox of Law Enforcement Press Conferences: A Comparative Study on Public Information and Suspects' Rights - Putri Rumondang Siagian; Hendri Hendri; Fahrizal S.Siagian (Universitas Muhammadiyah Purwokerto, 2026)
This study examines the balance between public access to information and the protection of suspects’ rights in the practice of law enforcement press conferences in Indonesia, as well as its comparison with international standards. Public access to information is a constitutional right guaranteed by the 1945 Constitution and the Law on Public Information Disclosure, yet in practice it often clashes with fundamental rights of suspects protected under the Criminal Procedure Code, such as the right to privacy, humane treatment, and the presumption of innocence. Press conferences frequently disclose suspects’ identities or images and present official narratives that may create public perceptions of guilt before a final court judgment. Such practices generate social stigma, undermine dignity, and violate the principle of due process of law. This normative legal research employs statutory and comparative approaches, showing that the United Kingdom and France impose strict restrictions on the publication of suspects’ identities, while Indonesia tends to resemble Thailand, where protection remains weak. The comparison highlights a regulatory gap in Indonesia, indicating the need for more detailed rules governing press conferences, limitations on disclosed information, and independent oversight mechanisms. Accordingly, a proportional balance between the public’s right to information and the protection of suspects’ rights can be realized within the framework of a democratic rule of law.